Altruism During Ebola: Risk Perception, Issue Salience, Cultural Cognition, and Information Processing. Issue 6 (14th December 2015) - Yang, Z. Janet
Abstract : A nationally representative sample of 1, 046 U.S. adults was randomly assigned to two experimental conditions that triggered different degrees of risk perception related to the Ebola outbreak. In the high‐risk condition, issue salience and deliberate processing increased individuals' altruistic behavioral intention. In contrast, cultural cognition worldview and negative emotions such as sadness and anger were significantly related to altruistic behavioral intention regardless of the experimental conditions. These findings suggest that affective responses diverge from cognitive processes in influencing risk‐related decisions. Practically, as the United States continues to send experts to the affected countries in West Africa, results from this study suggest meaningful pathways to improve risk communication intended to encourage more altruistic and pro‐social behaviors.